Steps toward a System of IRB Precedent: Piloting Approaches to Summarizing IRB Decisions for Future Use. Issue 6 (21st October 2021) - Seykora, Andrea; Coleman, Carl; Rosenfeld, Stephen J.; Bierer, Barbara E.; Lynch, Holly Fernandez
Abstract: Institutional review boards (IRBs) have been criticized for inconsistency and lack of transparency in decision‐making, problems that undermine both trust in their ability to protect human research participants and respect for their decisions among researchers. The absence of robust documentation of their decisions and the inability or unwillingness to share those decisions together represent a missed opportunity for IRBs to learn from one another and advance debates about challenging ethical issues. The concept of IRB precedent, modeled upon the system of legal precedent, has been proposed as a potential solution to these problems. In theory, an IRB faced with a review decision could look back at previous IRB decisions, either its own or those of other boards, made in similar studies or circumstances to guide the present decision. Some IRBs attempt this informally within their institution, but few examples of a structured system of IRB precedent have been described in the literature, and none has been widely adopted. This article describes a pilot project to summarize IRB decisions in a way that could facilitate their use as precedent by creating a documentation tool that meets four criteria—comprehensiveness, validity, searchability, and efficiency. Though this process turned out to be more challenging than expected, we identified key features of such a tool that holds promise for future development and could promote more consistent, robust IRB decision‐making and advance discourse in human research ethics.